THE USE OF FIGURATIVE ART OF WORDS IN THE POETRY OF SAIF FERGHANI (Scientific journal of the Fergana State University, 2024)
One of the continuous aspects of poetry is the use of artistic arts. Saif Farghani, like other poets, is adept at using image-creating elements. With all his knowledge and enthusiasm, he used the artistic arts skillfully and intelligently, and always refrained from repeating ideas. His actions are primarily aimed at creating new meanings. Therefore, the poet uses certain styles to make his thoughts colorful. Saif Farghani, along with other poets, often used artistic arts, which are one of the important elements of creativity, and thereby ensured the attractiveness, meaningfulness, impressiveness and beauty of his poetry. In this sense, many types of art are used in Saif Fargani's poetry, including allusion, allegory, talmeh, exaggeration, tazad, and diagnosis. possible In the use of each of the mentioned arts, Saif aimed for ways that are characteristic of his poetic skills and are rarely seen in other poets of Persian-Tajik literature.